Implementation of Cleaning Service Retribution Policy in Sidoarjo Regency : Implementasi Kebijakan Retribusi Pelayanan Kebersihan di Kabupaten Sidoarjo - Widya Ayu Pratiwi; Isna Fitria Agustina (Academia Open, 2022)
In the context of regional autonomy, each region is given full authority to regulate its own region by making policies that are oriented towards regional original income (PAD). One of the potential policies is waste retribution. To follow up on this, the Sidoarjo Regency Government issued Regional Regulation No. 6 of 2012 concerning Waste Management and Retribution for Waste/Cleaning Services. There is still miscommunication at the implementing level of the policy implementer level with the retribution obligors. Without any form of communication between the implementer and the mandatory waste retribution in Sidoarjo Regency, there are obstacles such as socialization, the community has not realized the obligation to pay the cleaning levy. The problem of low public understanding of the waste retribution policy is one of the factors for not achieving the revenue target of this policy.